Hubungan Tingkat Pengetahuan tentang PPOK dengan Ketaatan Pengobatan Pasien PPOK di RSUD Dr. Moewardi - Maria Dewi Caetline; Yusup Subagio Sutanto; Bhisma Murti (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2012)
Background: Chronic Obstructive Pulmonary Disease (COPD) is a non-infectious chronic and progressive disease, that has become one of the major causes of morbidity and mortality in the world. The treatment management of COPD is complex. Factors that can optimize treatment include patient acceptance to disease process, knowledge, trust in the treatment, effective patient-doctor communication, and adherence to treatment. This study aimed to analyze the association between knowledge of COPD and adherence to treatment among patients with COPD. Methods: This analytic study was observational with cross-sectional approach. A sample of 40 study subjects was selected by exhaustive sampling from outpatients with COPD visiting the Pulmonary Clinics, RSUD Dr. Moewardi Surakarta. The data were collected by interview using a set of questionnaire. The data was analyszed using multiple logistic regression model on SPSS version 17 for Windows. Results: Patients with high level of knowledge had 20 times as many level of adherence to COPD treatment than those with low level of knowledge (OR=21.01; 95%CI 2.08 to 211.98; p = 0.001). This estimate has controlled for the effects of confounding variables such as payment method, age, and gender. Conclusion: There is a statistically significant association between knowledge of COPD and adherence to treatment among patients with COPD. This conclusion is drawn after controlling for the effects of confounding factors such as payment method, age, and gender. Keywords: COPD, knowledge, adherence to treatment